Skin Microbiota in Contact Sports Athletes and Selection of Antiseptics for Professional Hygiene. (10th January 2019) - Martykanova, Dilyara S.; Davletova, Nailja Ch.; Zemlenuhin, Ilya A.; Volchkova, Venera I.; Mugallimov, Salavat M.; Ahatov, Azat M.; Laikov, Alexander V.; Markelova, Maria I.; Boulygina, Eugenia A.; Lopukhov, Leonid V.; Grigoryeva, Tatiana V.
Abstract : Background . The aim of this study was to assess changes in skin microbiota of wrestlers during training sessions and to determine the sensitivity of hemolytic bacterial isolates to antiseptics. Methods . The main skin bacterial isolates obtained from the skin of 15 wrestlers were identified by cultivation method, with the following MALDI Biotyper and 16S rRNA gene sequencing methods. The sensitivity of hemolytic isolates to antiseptics (Veltosept-2, Cutasept F, Chlorhexidine, Miramistin, and Hydrogen Peroxide) was evaluated by measuring the size of bacterial growth inhibition zone on agar plates. Results . Opportunistic bacteria of the species Bacillus cereus, Staphylococcus aureus, S. epidermidis, and S. saprophyticus were the most commonly found species in skin microbiota of wrestlers before and after training sessions. Representatives of all these species mostly had a hemolytic activity. An alcohol-containing antiseptic Veltosept-2 showed the strongest inhibitory effect on the bacterial isolates of athletes' skin microbiota most frequently detected in this study. Conclusions . The general increase in the bacterial colonization of wrestlers' skin, as well as the presence of hemolytic forms of opportunistic bacteria in cutaneous microbiota, indicates dysbiotic changes and a decrease in the protective features of the host organism. Veltosept-2 application can reduce the incidence of skin infections in contact sports athletes with the highest efficiency.